2016
DOI: 10.1257/mic.20140008
|View full text |Cite
|
Sign up to set email alerts
|

Separating Bayesian Updating from Non-Probabilistic Reasoning: An Experimental Investigation

Abstract: Through a series of decision tasks involving colored cards, we provide separate measures of Bayesian updating and non-probabilistic reasoning skills. We apply these measures to (and are the first to study) a common-value Dutch auction. This format is more salient than the strategically equivalent first-price auction and silent Dutch formats in hinting that one should condition one's estimate of the value on having the highest bid. Both Bayesian updating skills and non-probabilistic reasoning skills are shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…17 In columns 9-12 we estimate the same model as in columns 5-8 but exclude the first 3 periods in each session. After excluding the first three periods, there is no significant learning over time for any value of β in any treatment.…”
Section: 16mentioning
confidence: 99%
“…17 In columns 9-12 we estimate the same model as in columns 5-8 but exclude the first 3 periods in each session. After excluding the first three periods, there is no significant learning over time for any value of β in any treatment.…”
Section: 16mentioning
confidence: 99%
“…However, they focused on a different aspect of contingent reasoning, not directly related to the event of winning an auction. Finally, Levin, Peck, and Ivanov (2016) used Dutch auctions and showed that in this format conditioning on winning is more salient compared to a strategically equivalent first-price auction. All of these papers will be discussed in more detail in the following part.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A value of 0 is equivalent to the usual Bayesian Nash Equilibrium, whereas a value of 1 corresponds to a setting in which the players do not assume any correlation between the actions of a player and his type, which is also denoted as fully cursed equilibrium. 1 2015; Levin, Peck, and Ivanov, 2016;Esponda and Vespa, 2016;Li, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A value of 0 is equivalent to the usual Bayesian Nash Equilibrium, whereas a value of 1 corresponds to a setting in which the players do not assume any correlation between the actions of a player and his type, which is also denoted as fully cursed equilibrium. 1 2015; Levin, Peck, and Ivanov, 2016;Esponda and Vespa, 2016;Li, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally I only changed one parameter in stage II, whereas Koch and Penczynski (2014) used two different games, but with the same best-response functions and equilibria. Levin, Peck, and Ivanov (2016) used an experiment to investigate the impact of Bayesian updating and non-probabilistic reasoning (referred to as contingent reasoning in this paper) on avoiding the winner's curse. They used common value Dutch and common value first-price auctions based on the model in Kagel, Harstad, and Levin (1987) and compared both versions to quantify the effect of non-probabilistic reasoning.…”
mentioning
confidence: 99%